Attitude of Graduates of Requalification Studies, Providing Pedagogue’s Qualification, To Teachers’ Activity - Ušeckienė, Lidija; Bakutytė, Rima (Pedagogika, 2013)
During the recent decade the university teacher’s activity is quite extensively analyzed from various perspectives in Lithuania and abroad. However, there is a lack of researches analyzing the opinion of persons who attended requalification courses about teachers. The research aim is to find out activity parameters of teachers teaching in requalification studies and the opinion of graduates of pedagogical requalification studies, who differ in age and have acquired varying work experience, about teachers’ activity during studies. Research methods: content analysis of pedagogical scientific literature and documents on education; graduates’ questionnaire survey; descriptive statistics; correlation analysis, factor analysis. The research was conducted in 2011. The research included 81 persons who acquired the pedagogue’s qualification at one of university type continuous studies institutions of Lithuania, who are of different ages and have different work experience. Research results proved that based on factor analysis results, activities of teachers working in requalification studies can be evaluated according to the following parameters: development of problem solving and information literacy abilities (incitement to independently look for problem solution, raising of problems that earlier were not envisaged, grounding on one’s research results, justification of statements on the basis of other researchers’ data, proposal to study additional literature, usage of newest literature sources, proposal to use teachers’ prepared teaching textbooks, data bases, analyze literature in the foreign language, familiarization with programme aims and content); stimulation of cognitive activities (application of individual research, case analysis, application of brainstorming, proposal to prepare projects, implementation of students’ proposed projects, support preparing the competence portfolio, consideration of students’ wishes, asking students’ opinion, permission to choose assignments, interesting way of delivering); promotion of reflection on experience (application of reflection on action, experiential analysis, games, analysis of professional activity problems, proposal of ways of solving them, justification of one’s opinion); promotion of consistent and systematic learning (incitement to work systematically, emphasis on critical statements, sequential delivering of materials, its understandable explanation, visual presentation of information). Research results of graduates’ opinion disclosed that teachers working in requalification studies in principal focused on all areas of their activity. They have particularly developed graduates’ ability of problem solving and information literacy, accustomed students to work systematically and consistently. Teachers less promoted reflection on experience and least, cognitive activity.